Principal Diagnoses in Psychiatric Outpatients With Posttraumatic Stress Disorder: Implications for Screening Recommendations. Issue 4 (April 2020) - Kiefer, Reina; Chelminski, Iwona; Dalrymple, Kristy; Zimmerman, Mark
Abstract : Abstract: In this study, we examined the prevalence of posttraumatic stress disorder (PTSD) in 3800 psychiatric outpatients with different principal diagnoses. For all disorders identified as a principal diagnosis, we compared patients' odds ratios of PTSD to all other patients in the sample. Approximately one-sixth of the sample ( n = 663, 17.4%) was diagnosed with PTSD, including 417 patients with current PTSD and 246 with PTSD in partial remission. Patients with principal bipolar disorder and major depressive disorder (MDD) demonstrated higher rates of PTSD compared with those without principal bipolar and MDD. For most psychiatric outpatients with PTSD, the principal diagnosis for which they seek treatment is not PTSD, but rather a mood disorder. This highlights the importance of screening for PTSD, particularly in patients with a principal diagnosis for which the prevalence of PTSD is relatively high, namely, MDD, bipolar disorder, panic disorder, and borderline personality disorder.